Analysis of changes in flood regime using a distributed hydrological model: a case study in the Second Songhua River basin, China. Issue 3 (4th May 2018) - Wang, Mingyuan; Lei, Xiaohui; Liao, Weihong; Shang, Yizi
Abstract: This study proposes and tests a new approach to detect and analyze changes in flood regime using a distributed hydrological model (EasyDHM), using the Second Songhua River basin, China, as a case study. Model calibration and parameter sensitivity were used to represent flood regimes in a 60-year series (1954–2013), with three different flood regime periods identified. The changes in flood regime were estimated by model parameters, flood result residuals and the overall process in the hydrological model in the three periods. The results show that human activities significantly impacted flood regimes, with significant flood regime change largely attributed to increases in water storage in multiple small reservoirs. Flood volume was reduced significantly between the periods in all three watersheds. The parameters also changed in variety between the periods. The study highlights the importance of incorporating data on small-reservoir constructions in flood control systems.